ASME 2020 Conference on Smart Materials, Adaptive Structures and Intelligent Systems 2020
DOI: 10.1115/smasis2020-2328
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling of a Segmented Bimorph Lithium Ion Battery Actuator

Abstract: Silicon composite anode-based lithium ion battery actuators have strong potential for large actuation strain, complex shape change, and large compliance tunability. This allows for actuators with potential to do work with no energy expenditure beyond parasitic losses to internal resistance. This paper studies a segmented bimorph actuator comprised of a silicon-based composite anode double-side coated on copper foil. The bimorph design allows for a nearly 360° range of motion in transverse bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Models of unimorph (Gonzalez et al, 2021) and bimorph (Gonzalez et al, 2020) LIBs have been published previously by the authors and are reviewed briefly here. A schematic for an N Layer , N Seg multimorph is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Models of unimorph (Gonzalez et al, 2021) and bimorph (Gonzalez et al, 2020) LIBs have been published previously by the authors and are reviewed briefly here. A schematic for an N Layer , N Seg multimorph is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The authors have previously reported the derivation of the actuator metrics here for a unimorph and the free deflection of a bimorph (Gonzalez et al, 2020, 2021). The free deflection and blocked deflection are found by taking the free curvature κ j and finding the local deflections, then using a transformation of coordinates to find the global deflections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations